Pain Assessment in Palliative Medicine: Review of Pain Rating Scales - Kotowicz, Michał; Zielińska, Magdalena; Szajewski, Paweł; Zagórska, Aleksandra; Joanna Ciećwierz; Koczkodaj, Maria; Bieniak-Pentchev, Magdalena (Quality in Sport, 2026)
Pain is one of the most prevalent and distressingsymptoms in patients receiving palliative care, oftenleading to a profound reduction in quality of life. Effectivepain control requires accurate and systematic assessment, yet the multidimensional and subjective nature of painmakes this process complex. This review summarizes the most commonly used pain rating tools in palliativemedicine, including the Numeric Rating Scale (NRS), Visual Analog Scale (VAS), Verbal Rating Scale (VRS), Wong–Baker FACES Pain Rating Scale (WBS), FLACC Scale, McGill Pain Questionnaire (MPQ), and Abbey PainScale (APS). Each scale’s characteristics, advantages, and limitations are discussed in relation to different patientpopulations, such as cognitively impaired or non-verbalindividuals. The article emphasizes that the choice of assessment tool should be individualized, reflecting the patient’s clinical condition, communication ability, and cognitive status. Accurate pain assessment forms the foundation of effective analgesic therapy and improvedpatient outcomes in palliative medicine.